Convergent and Divergent Signaling in PAMP-Triggered Immunity and Effector-Triggered Immunity - Peng, Yujun; van Wersch, Rowan; Zhang, Yuelin (Molecular plant-microbe interactions, 2018)
Plants use diverse immune receptors to sense pathogen attacks. Recognition of pathogen-associated molecular patterns (PAMPs) by pattern recognition receptors localized on the plasma membrane leads to PAMP-triggered immunity (PTI). Detection of pathogen effectors by intracellular or plasma membrane–localized immune receptors results in effector-triggered immunity (ETI). Despite the large variations in the magnitude and duration of immune responses triggered by different PAMPs or pathogen effectors during PTI and ETI, plasma membrane–localized immune receptors activate similar downstream molecular events such as mitogen-activated protein kinase activation, oxidative burst, ion influx, and increased biosynthesis of plant defense hormones, indicating that defense signals initiated at the plasma membrane converge at later points. On the other hand, activation of ETI by immune receptors localized to the nucleus appears to be more directly associated with transcriptional regulation of defense gene expression. Here, we review recent progress in signal transductions downstream of different groups of plant immune receptors, highlighting the converging and diverging molecular events.